Improving Wireless Power Transfer Efficiency Considering Rectifier Input Impedance and Load Quality Factor - Somar Ghadeer; Nasrin Rezaei-Hosseinabadi; Ahmadreza Tabesh; S. Ali Khajehoddin (IEEE Access, 2023)
This paper presents a method to maximize power transfer efficiency (PTE) in wireless power transfer (WPT) systems with low-quality factors merely based on tuning the receiver-side components. The paper also suggests an algorithm to find the optimum components values considering the effect of input impedance of receiver-side rectifier at high-frequency (MHz) applications such as portable electronic devices. Existing methods often consider the input impedance of the full-bridge rectifier as a pure resistance at low frequencies. However, at high frequencies, the complex impedance of the rectifier should be taken into account since it impacts on the components optimum values to maximize PTE. Despite conventional maximizing PTE methods for series-series and series-parallel topologies, this paper shows that a series-parallel WPT system with low load quality factor requires adjusting the resonant capacitor in addition to resistive load. The validity of the proposed method is verified based on numerical simulations and experiment tests using a 100 mW cm-scale prototype of a resonant inductive link at 6.78 MHz with varying distance between coils. The test results show a PTE improvement up to 40% in a series-parallel WPT compared with the methods that only tune the load equivalent resistance.